IMPLEMENTATION OF THE HABIT OF DHUHA PRAYER IN FORMING THE RELIGIOUS CHARACTER OF STUDENTS AT MIS ROHMATUL UMMAH MOMPANG JAE - Halimatus Sakdiah; Mutiah Lbs; Nur Kholilah; Riski Saskia Ray; Namiroh Lubis (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to describe the implementation of the Dhuha prayer habit and analyze its role in shaping the religious character of students at MIS Rohmatul Ummah Mompang Jae. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, Islamic Religious Education teachers, students, and parents. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Dhuha prayer habit at MIS Rohmatul Ummah Mompang Jae has been implemented routinely and programmed every day with teacher guidance. This activity is able to increase discipline, awareness of worship, and instill religious values ​​such as responsibility, politeness, and gratitude in students. In addition, the Dhuha prayer habit also has a positive impact on student behavior in the family environment, marked by increased awareness of worship and respect for parents. Thus, it can be concluded that the implementation of the Dhuha prayer habit plays an effective role in shaping students' religious character in a sustainable manner.